STAN Nigerian Integrated Science Project Workbook Two - Nwaiwu et al (Heinemann Educational Books (Nig.) Plc, 1972)
This book has written because of the need to fit the syllabus into the three year junior secondary schools system.
Keywords: Juvenile literature-Integrated Science-Study and teaching (Secondary)-Nigeria (English)